Development of Healthy Life Behavior Model in The Institution of Education - Agus Amin Sulistiono; Lucia H. Winingsih (AIBPM Publisher, 2020)
Healthy Active lifestyle through 1) being fond of movement, 2) caring for one's own health, 3) caring for the health of others, and 4) caring for the environment, which is closely related to the government's commitment to the healthy life behavior program. The result shows that classes that carry out Healthy Active Living behavior resulted in an increase in students' physical fitness, while control classes that did not carry out Healthy Active Life behavior did not significantly increase physical fitness. There is a positive correlation between Healthy Active Life and physical fitness and health. How to live a healthy active life as a model for improving one's own health, common health, environmental health and fitness can be an important step to maintain health.